Chemical Characterization of Secondary Metabolite from the Endophytic Fungus Trichordema reecei isolated from The Twig of Syzygium aqueum - Ummi Hiras Habisukan; Elfita Elfita; Hary Widjajanti; Arum Setiawan (Science and Technology Indonesia, 2021)
Endophytic fungi are microorganisms that live in plants, without negative effects and are mutually related to hosting plants. Exploration of bioactive compounds from Endophytic fungi is easier and cheaper because they do not require a large area, a short growing time, and uncomplicated mixed compounds. Endophytic fungi are new and patent base secondary metabolites but they are not extensively characterized and investigated for the exploration of raw materials for drugs. The purpose of this study was to obtain antioxidant secondary metabolites from Endophytic fungi that live in the Syzygium aqueum medicinal plant. In this study, Endophyticfungi were isolated from S. aqueum twigs and molecular identification. The secondary metabolites were isolated by chromatographic method and chemical structure identified by spectroscopy. Antioxidant activity was evaluated by method 1,1diphenyl-2-picryl hydrazyl (DPPH). Phylogenetic analysis showed the Endophytic fungi of S. aqueum twig have a high similarity with the Trichordema reecei twig 19MSr.B2.3. The secondary metabolites from the ethyl acetate extract of the liquid culture of the fungus were identified as (4-hydroxy-3-(4-hydroxyphenyl)-5 oxotetrahydrofuran-2-yl) methyl acetate with IC50= 75.13 ????g/mL. The secondary metabolites can be developed into starting molecules for potential antioxidant agents.